Assessing Reassessment of Kerala Model - K T RAMMOHAN (Economic and Political Weekly April 8, 2000, 2000)
A series of scholarly inquiries initiated from the mid-1980s questioning Kerala's deficient economic, industrial development are increasingly exposing the failings of the `Kerala Model' of social development. But the new social anthropology of Kerala's development merely combines the colonial view with neoliberalism, and fails to fulfil its promise